Geochemical data of rare earth-enriched sediments from the Western, Central North, and Eastern South Pacific - Liao, Jianlin; Chen, Jieyun; Sun, Xiaoming; Deng, Yinan; Wang, Yanjingyu; Wang, Dajin; Hong, Gang; Klose, Lukas; Koschinsky, Andrea (PANGAEA, 2023)
Major and trace elements of four gravity sediments cores retrieved from the Western (159°46′E, 17°23′N), Central North (161°30′W, 13°14′N), and Eastern South Pacific (135°15′W, 14°46′S, and 129°6′W, 13°47′S) were analyzed in order to research the enrichment mechanism of rare earth elements in deep-sea sediments. Four representative layers of each core were treated by sequential extraction to separate mineral phases including Ca-phosphate, Mn oxides, Fe oxides, etc. The major and trace elements of the leaching solutions were measured to estimate the proportions of rare earth elements controlled by different mineral phases.
Keywords: Gravity core; Pacific; Rare earth elements and yttrium; Sequential extraction